Succinyl-CoA:(R)-Benzylsuccinate CoA-Transferase: an Enzyme of the Anaerobic Toluene Catabolic Pathway in Denitrifying Bacteria - Leutwein, Christina (American Society for Microbiology, 2001)
Anaerobic microbial toluene catabolism is initiated by addition of fumarate to the methyl group of toluene, yielding (R)-benzylsuccinate as first intermediate, which is further metabolized via β-oxidation to benzoyl-coenzyme A (CoA) and succinyl-CoA. A specific succinyl-CoA:(R)-benzylsuccinate CoA-transferase activating (R)-benzylsuccinate to the CoA-thioester was purified and characterized from Thauera aromatica. The enzyme is fully reversible and forms exclusively the 2-(R)-benzylsuccinyl-CoA isomer. Only some close chemical analogs of the substrates are accepted by the enzyme: succinate was partially replaced by maleate or methylsuccinate, and (R)-benzylsuccinate was replaced by methylsuccinate, benzylmalonate, or phenylsuccinate. In contrast to all other known CoA-transferases, the enzyme consists of two subunits of similar amino acid sequences and similar sizes (44 and 45 kDa) in an α(2)β(2) conformation. Identity of the subunits with the products of the previously identified toluene-induced bbsEF genes was confirmed by determination of the exact masses via electrospray-mass spectrometry. The deduced amino acid sequences resemble those of only two other characterized CoA-transferases, oxalyl-CoA:formate CoA-transferase and (E)-cinnamoyl-CoA:(R)-phenyllactate CoA-transferase, which represent a new family of CoA-transferases. As suggested by kinetic analysis, the reaction mechanism of enzymes of this family apparently involves formation of a ternary complex between the enzyme and the two substrates.